Safety and efficacy of 532 nm frequency-doubled Nd-YAG green laser photocoagulation for treatment of retinopathy of prematurity - Simar Rajan Singh; Deeksha Katoch; Sabia Handa; Savleen Kaur; Bruttendu Moharana; Mohit Dogra; Mangat R Dogra (Indian Journal of Ophthalmology, 2019)
Purpose: To evaluate the safety and efficacy of 532 nm frequency-doubled Nd-YAG green laser for treatment of retinopathy of prematurity (ROP). Methods: This retrospective interventional case series included infants undergoing treatment for ROP with 532 nm green laser between January 2012 and March 2017 at a single tertiary-care referral center. Review of clinical records was done to identify baseline ROP characteristics, procedural difficulties, complications related to the laser procedure and outcome of treatment at ≥ 1 year of follow-up. Results: There are about 347 eyes of 182 infants were included in this present study. ROP presented in zone I in 76 eyes (21.9%) and zone II in 271 eyes (78.1%). Tunica vasculosa lentis (TVL) was present in 43.8% and pre-existing vitreous hemorrhage in 4.6% of the eyes. 532 nm green laser could be performed as a primary procedure in all eyes, including those with TVL. 322 eyes completed a minimum follow up of 1 year with a mean follow up of 22.8 months (range, 12–54 months). At the last follow-up visit, 298 (92.5%) of the 322 eyes had a favorable outcome. On logistic regression analysis, pre-existing fibrovascular proliferation (p = 0.04) and new-onset fibrovascular proliferation after treatment (p = 0.001) were the most significant independent predictors of poor outcome. Complications encountered were new-onset hemorrhage in 36 eyes (11.2%), anterior segment ischemia in two eyes (0.006%) and cataract in one eye (0.003%). Conclusion: 532 nm frequency-doubled Nd-YAG green laser appears to be safe and effective in the treatment of ROP.